Abundant Interaction Solutions of Sine-Gordon Equation - DaZhao Lü; YanYing Cui; ChangHe Liu; ShangWen Wu (Journal of Applied Mathematics)
With the help of computer symbolic computation software (e.g., Maple), abundant interaction solutions of sine-Gordon equation are obtained by means of a constructed Wronskian form expansion method. The method is based upon the forms and structures of Wronskian solutions of sine-Gordon equation, and the functions used in the Wronskian determinants do not satisfy linear partial differential equations. Such interaction solutions are difficultly obtained via other methods. And the method can be automatically carried out in computer.